THE USE OF A METHOD OF LIFT PUMP FOR CIRCULATING SOLUTION IN THE CHEMICAL DESCALING OF THE BOILER DKVR-4/13 - Viktorov, V. H.; Kravets, V. V.; Kholoimov, V. A.; Khrystian, Ye. V. (Science and Transport Progress, 2004)
The article represents practical studies on using the method of airlift for circulations of solution in chemical cleaning of the caldron DKVR-4/13 from scum and describes the main technological schemes of the method. The authors show that application of the method allows reducing the time of chemical washing of the caldron nearly twofold in comparison with existing methods, and rids of the necessity of using powerful and expensive pumps.